Clinical associates and access to healthcare in the Eastern Cape province of South Africa - Grace Isembatya; Aloysious Kakia; Jehu E. Iputo (AOSIS, 2022)
Background: Clinical associates (ClinAs) were introduced into South Africa as part of the remedy for the severe shortage of healthcare workers in rural areas. Walter Sisulu University (WSU) graduated 100 ClinAs between 2011 and 2014. These ClinAs were expected to be based at district hospitals where they would work under the supervision of doctors, reduce the workload of doctors and increase access to healthcare in the Eastern Cape. Aim: This study aimed to examine the role played by ClinAs in healthcare delivery in Eastern Cape district hospitals, and to determine whether the training of ClinAs adequately prepared them for this role. Setting: The study was conducted in the Eastern Cape province of South Africa amongst ClinAs who graduated from WSU between 2011 and 2014, and healthcare workers from Madzikane KaZulu Memorial Hospital. Methods: This was an exploratory cross-sectional mixed methods study with a convergent design. Surveys and in-depth interviews were conducted amongst ClinAs, nurses, doctors and one pharmacist. Both qualitative and quantitative data were analysed and reported. Results: Clinical associates are seen to improve the workload of doctors, and to increase access to healthcare. Thirty-four percent of ClinAs were no longer contributing to healthcare in the Eastern Cape. Conclusion: Clinical associates are making a significant contribution to access to healthcare in the Eastern Cape. Their supervision regimen needs to be revisited and factors that contribute to the attrition of ClinAs in the Eastern Cape need to be addressed.